2018
DOI: 10.1038/s41598-018-30648-7
|View full text |Cite
|
Sign up to set email alerts
|

High expression of EZH2 as a marker for the differential diagnosis of malignant and benign myogenic tumors

Abstract: Overlap in morphologic features between malignant and benign myogenic tumors, such as leiomyosarcoma (LMS) vs. leiomyoma as well as rhabdomyosarcoma (RMS) vs. rhabdomyoma, often makes differential diagnosis difficult and challenging. Here the expressions of Enhancer of Zeste Homolog 2 (EZH2), Suppressor of Zeste 12 (SUZ12), retinoblastoma protein associated protein 46 (RbAp46), Embryonic Ectoderm Development (EED) and ki-67 protein were detected by immunohistochemistry to evaluate their values in differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
(23 reference statements)
2
8
0
Order By: Relevance
“…The subgroup analysis in those previously published studies showed that high EZH2 expression remained as a highly sensitive and specific marker in distinguishing lower grade malignancies from benign neoplasms (e.g., well‐differentiated leiomyosarcoma vs. leiomyoma) 6,7 . Similar to the findings of the previous studies, the current study has shown that EZH2 might be a promising marker to distinguish fibromatosis‐like MBC from the benign spindle cell neoplasms of the breast such as fibromatosis, therefore, larger studies should confirm this finding.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The subgroup analysis in those previously published studies showed that high EZH2 expression remained as a highly sensitive and specific marker in distinguishing lower grade malignancies from benign neoplasms (e.g., well‐differentiated leiomyosarcoma vs. leiomyoma) 6,7 . Similar to the findings of the previous studies, the current study has shown that EZH2 might be a promising marker to distinguish fibromatosis‐like MBC from the benign spindle cell neoplasms of the breast such as fibromatosis, therefore, larger studies should confirm this finding.…”
Section: Discussionsupporting
confidence: 88%
“…The main significance of EZH2 overexpression in cancer, including breast cancer, is that high EZH2 expression is usually associated with worse pathologic features, invasion, metastasis and poor clinical outcome 3,9–13 . Apart from its clinical‐related significance, the diagnostic utility of EZH2 expression was previously evaluated to differentiate malignant tumors from their benign counterparts in many organs such as cervix, mesothelium, myometrium and shown to be a promising diagnostic marker 6,7,14,14,15 . As spindle cell lesions of the breast are one of the challenging diagnostic areas for pathologists, we explored the significance of EZH2 expression in distinguishing benign and malignant spindle cell tumors of the breast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, EZH2 is overexpressed in many STS in comparison to normal tissue, which may be attributed to the cell of origin of these tumours. STS are thought to be derived from mesenchymal stem cells, where the balance of EZH2 expression along with other histone modifying enzymes is thought to control the differentiation lineage process [16][17][18][19] . The reason why overexpression of wildtype EZH2 leads to associated poor outcomes can primarily be understood in terms of the normal function of EZH2.…”
Section: Role Of Ezh2 In Stsmentioning
confidence: 99%
“…The abundance of EZH2 protein in RMS and its association with poor prognosis, increased metastasis and lymph node involvement make EZH2 an interesting therapeutic target [ 24 , 25 , 26 ]. Different approaches to affect EZH2 have been investigated [ 27 ].…”
Section: Introductionmentioning
confidence: 99%